2006
DOI: 10.1016/j.molcel.2006.03.038
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Gene Per1 Plays an Important Role in Cell Growth and DNA Damage Control in Human Cancer Cells

Abstract: The Per1 gene is a core clock factor that plays an essential role in generating circadian rhythms. Recent data reveal that major biological pathways, including those critical to cell division, are under circadian control. We report here that Per1 provides an important link between the circadian system and the cell cycle system. Overexpression of Per1 sensitized human cancer cells to DNA damage-induced apoptosis; in contrast, inhibition of Per1 in similarly treated cells blunted apoptosis. The apoptotic phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
518
2
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(568 citation statements)
references
References 36 publications
21
518
2
21
Order By: Relevance
“…It has been shown that two clock proteins, Per1 and Prd4, have integral roles in the ATM-Chk2 DDR pathway 10,11 . Here, we show that HCLK2, an uncharacterized orphan mammalian protein with weak similarity to the C. elegans biological clock protein CLK-2, interacts with components of the S-phase checkpoint and has a critical role in this checkpoint and the subsequent activation of both Fanconi anaemia and homologousrecombination repair responses.…”
mentioning
confidence: 99%
“…It has been shown that two clock proteins, Per1 and Prd4, have integral roles in the ATM-Chk2 DDR pathway 10,11 . Here, we show that HCLK2, an uncharacterized orphan mammalian protein with weak similarity to the C. elegans biological clock protein CLK-2, interacts with components of the S-phase checkpoint and has a critical role in this checkpoint and the subsequent activation of both Fanconi anaemia and homologousrecombination repair responses.…”
mentioning
confidence: 99%
“…25,27) In addition, PER1 interacts with crucial components of cellular stress response pathways including the ataxia telangiectasia mutated (ATM) and checkpoint kinase 2 (Chk2) proteins. 28) Accordingly, ectopic expression of PER1 or PER2 results in cell growth inhibition, cell cycle arrest, apoptosis, or loss of clonogenic capacity. [28][29][30] PER1 and PER2 also interact with the androgen receptor (AR) or estrogen receptor (ER), respectively, in that PER1 inhibits AR-dependent transcription and PER2 induces ER degradation.…”
Section: The Physiological Functions Of Core Circa-dian Regulatorsmentioning
confidence: 99%
“…28) Accordingly, ectopic expression of PER1 or PER2 results in cell growth inhibition, cell cycle arrest, apoptosis, or loss of clonogenic capacity. [28][29][30] PER1 and PER2 also interact with the androgen receptor (AR) or estrogen receptor (ER), respectively, in that PER1 inhibits AR-dependent transcription and PER2 induces ER degradation. 31,32) These findings are consistent with the idea that clock proteins act as key players in the cell cycle and DDR by interacting directly with and regulating the functions of the proteins mediating these processes.…”
Section: The Physiological Functions Of Core Circa-dian Regulatorsmentioning
confidence: 99%
“…Accelerated tumor development in response to circadian disruption and clock gene deregulation has been recorded. Transcription upregulation of Per1 and Per2 blocks breast-cancer cell proliferation [124] probably by induced cell apoptosis [125]. Per2 has been demonstrated to be a tumor suppressor gene in MCF-7 breast cancer epithelial cells [126] by linking the Estrogenreceptor-α (ER-α) to the circadian system regulating its degradation [127].…”
Section: Circadian Clock and Breast Cancermentioning
confidence: 99%